2011
DOI: 10.1111/j.1469-0691.2011.03642.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuroinvasive West Nile virus infections during the outbreak in Greece

Abstract: A major outbreak of West Nile virus (WNV) infections took place in 2010 in Greece. Apart from the neuroinvasive cases, many additional cases without involvement of the nervous system were observed, characterized by high fever, myalgia, rash, leukopenia, and long-lasting recovery. West Nile non-neuroinvasive disease is a distinct clinical syndrome, and is not always mild.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Of the 197 WNV neuroinvasive cases reported, 33 were fatal ( 3 ). Many nonneuroinvasive cases were observed ( 4 ). A lineage 2 WNV (Nea Santa-Greece-2010 strain) was detected in Culex pipiens mosquitoes collected at 2 locations where WNV cases had been reported ( 5 ).…”
mentioning
confidence: 99%
“…Of the 197 WNV neuroinvasive cases reported, 33 were fatal ( 3 ). Many nonneuroinvasive cases were observed ( 4 ). A lineage 2 WNV (Nea Santa-Greece-2010 strain) was detected in Culex pipiens mosquitoes collected at 2 locations where WNV cases had been reported ( 5 ).…”
mentioning
confidence: 99%
“…A follow-up study in WNF patients demonstrated that fatigue and weakness lasted for almost a month since the onset of the symptoms [91]. A study among Greek patients with WNF showed that many of the patients presented persistence of fever, intense malaise or even experienced weight loss [93]. A long-lasting recovery of several days or even months, suggest that WNF is not always mild [93].…”
Section: Wnv In Humansmentioning
confidence: 99%
“…A study among Greek patients with WNF showed that many of the patients presented persistence of fever, intense malaise or even experienced weight loss [93]. A long-lasting recovery of several days or even months, suggest that WNF is not always mild [93]. Approximately 1% of the patients with WNV infection present symptoms from the nervous system; primary target of WNV in the brain and spinal cord are the neurons.…”
Section: Wnv In Humansmentioning
confidence: 99%
“…Lineage 2 viruses have been found primarily in southern and central Africa, where they are usually associated with systemic febrile illness without involvement of the central nervous system (CNS). Recent geographic spread of lineage 2 viruses has been observed in the Mediterranean region and Europe and a recent outbreak due to a lineage 2 virus resulted in cases of severe human neurologic illness in Greece in 2010 (Anastasiadou et al 2011;Danis et al 2011a, b;.…”
Section: Prevention Of Human Rabiesmentioning
confidence: 99%